Bioconversion of barley straw lignin into biodiesel using Rhodococcus sp. YHY01. (October 2019) - Bhatia, Shashi Kant; Gurav, Ranjit; Choi, Tae-Rim; Han, Yeong Hoon; Park, Ye-Lim; Park, Jun Young; Jung, Hye-Rim; Yang, Soo-Yeon; Song, Hun-Suk; Kim, Sang-Hyoun; Choi, Kwon-Young; Yang, Yung-Hun
Graphical abstract: Highlights: Rhodococcus sp. YHY01 can utilize p -coumaric acid > cresol > 2, 6 dimethoxyphenol. IC50 value was; p -coumaric (13.4 mM), cresol (7.9 mM), 2, 6 dimethoxyphenol (3.4 mM) Biomass and lipid production in order; p -coumaric acid > cresol > 2, 6 dimethoxyphenol. Barley lignin led to 39% w/w lipid accumulation in Rhodococcus sp. YHY01. Abstract: Rhodococcus sp. YHY01 was studied to utilize various lignin derived aromatic compounds. It was able to utilize p -coumaric acid, cresol, and 2, 6 dimethoxyphenol and resulted in biomass production i.e. 0.38 g dcw/L, 0.25 g dcw/L and 0.1 g dcw/L, and lipid accumulation i.e. 49%, 40%, 30%, respectively. The half maximal inhibitory concentration (IC50 ) value for p -coumaric acid (13.4 mM), cresol (7.9 mM), and 2, 6 dimethoxyphenol (3.4 mM) was analyzed. Dimethyl sulfoxide (DMSO) solubilized barley straw lignin fraction was used as a carbon source for Rhodococcus sp. YHY01 and resulted in 0.130 g dcw/L with 39% w/w lipid accumulation. Major fatty acids were palmitic acid (C16:0) 51.87%, palmitoleic acid (C16:l) 14.90%, and oleic acid (C18:1) 13.76%, respectively. Properties of biodiesel produced from barley straw lignin were as iodine value (IV) 27.25, cetane number (CN) 65.57, cold filter plugging point (CFPP) 14.36, viscosity (υ) 3.81, and density (ρ) 0.86.